Impact of antiphospholipid antibodies on heart valve involvements in systemic lupus erythematosus: based on CSTAR cohort - Wei Bai; Shangzhu Zhang; Xiaofeng Zeng; Hui Jiang; Jiuliang Zhao; Mengtao Li; Yan Zhao; Junyan Qian; Ziqian Wang; Can Huang; Yuan Zhao; Xiaoxiao Guo; et al. (Lupus Science and Medicine)
Objective This study aims to evaluate the role of antiphospholipid antibodies (aPLs) in patients with SLE with heart valve diseases (HVDs).Methods This prospective study included consecutive patients with SLE who visited Peking Union Medical College Hospital between April 1999 and December 2024. Echocardiography was performed based on clinical indications. Clinical characteristics, aPL profiles and echocardiographic findings were collected. Logistic regression was used to evaluate associations between aPLs and HVD.Results Among 508 patients with SLE, 27.4% had HVD. The most frequently affected valves were aortic (17.3%) and mitral (11.2%) valves, with thickening (19.5%) and regurgitation (15.9%) as the leading lesion types. aPLs positive patients with SLE had higher rates of HVD (35.1% vs 24.0%, p=0.010), including valve thickening (25.3% vs 16.9%, p=0.028), regurgitation (24.7% vs 12.1%, p<0.001), vegetations (9.1% vs 0.8%, p<0.001) and stenosis (1.9% vs 0.0%, p=0.008). Anticardiolipin-IgG was associated with HVD (OR=2.484, p=0.003), mitral lesions (OR=4.156, p<0.001), valve thickening (OR=2.255, p=0.011) and regurgitation (OR=2.121, p=0.014). Anti-β2 glycoprotein I-IgG showed similar associations and was also linked to valve stenosis (OR=11.209, p=0.022). Lupus anticoagulant (LA) was associated with valve vegetations (OR=8.659, p<0.001) and interventional/surgical indications (OR=6.868, p=0.005).Conclusion aPLs, especially IgG isotype and LA, are independently associated with diverse HVD in SLE. Echocardiographic monitoring is warranted in aPL-positive patients.